Muhammad Ali, Kinshasa 1974 - Morvan, Jean David (Titan Comics, 2021)
Using both documentary photographs and graphic novel illustrations, reveals the context of the "Rumble in the Jungle" boxing match between Muhammad Ali and George Foreman in 1974.